Achievement and competitiveness in elite youth basketball: what matters? - Gonçalves, Carlos E. (2015)
In a previous study we described the achievement and motivation variables that can explain the belonging to an elite competitive level of young basketball players, divided in two groups: elite and local. Two questionnaires were used: the Work and Family Orientation Questionnaire/WOFO (Spence and Helmreich, 1983), with three dimensions of achievement: work, mastery and competitiveness, and the Deliberate Practice Motivation Questionnaire/DPMQ (De Bruin et al., 2007), which assesses two dimensions of deliberate practice: will to compete and will to excel. Sixty-four male and fifty-two female basketball players under 16 years (mean age 15.4±0.91) participated in this study. A second group of players (14 males and 14 females) was obtained from those who were selected to play for the regional teams competing in the national youth festival. To compare the selected with the non-selected athletes, logistic regression was used. All the parameters, except mastery, explain the possibility to belong to the elite group, with will to compete and will to excel at the top of the discriminant variables. Once again, the findings suggest that a self-orientation to excellence may play a crucial role in ambition to reach higher standards in competition. The will to reach excellence in performance can be considered as a condition to aspire to participate in more specialized and demanding practice. The present study overcame the limitations of previous research regarding the selection moment, and globally confirmed the findings. The crucial need of inter-disciplinary, longitudinal research is stressed, because the path to expertise in sport is only meaningful over a long period of time